Media Framing of CNN Indonesia and Kompas.com on the Israeli-Palestinian Conflict - Maulana, Muhammad Iqbal; Febriana, Poppy (Indonesian Journal of Cultural and Community Development, 2025)
General Background: The Israel-Palestine conflict remains a contentious global issue, particularly as tensions escalate, drawing renewed attention to the actions of Hamas in late 2023. Specific Background: This study analyzes how CNN Indonesia and Kompas.com frame and present information regarding the territorial conflict, emphasizing the role of media in shaping public perception. Knowledge Gap: While previous studies have examined media representations of conflicts, there is a lack of focused analysis on Indonesian news outlets and their framing techniques in this specific context. Aims: The research aims to investigate the construction and presentation of narratives surrounding the Israel-Palestine conflict by CNN Indonesia and Kompas.com using a syntactic analysis approach based on the inverted pyramid structure. Results: The findings indicate that both media outlets exhibit similarities in their reporting but also highlight notable differences in titles and accompanying imagery. Novelty: This study contributes to the understanding of how Indonesian media frame complex international conflicts, revealing implicit meanings that may influence public discourse. Implications: The results underscore the importance of media framing in shaping narratives about the Israel-Palestine conflict, informing future research and media literacy initiatives that address the impacts of news representation on public understanding. Highlights: Both CNN Indonesia and Kompas.com display similarities and differences in titles and imagery. Framing techniques significantly influence public perception of international conflicts. The inverted pyramid structure is used to analyze news narratives, revealing deeper implicit meanings. Keywords - Israel-Palestine, Media, Framing, Syntactic, Conflict